Multi-Interpenetrating Network (IPN) Hydrogel by Gelatin and Silk Fibroin - Park, Shiwha (Biomater Sci, 2019)
A mechanically strong composite hydrogel was produced based on the interpenetrating network (IPN) between gelatin and silk fibroin. When two layers of IPN was created, the resulting hydrogel exhibited much improved mechanical properties. This hydrogel is biodegradable, non-cytotoxic and allows cell adhesion and proliferation on the surface.